2015
DOI: 10.1002/sm2.94
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Clinical Features, Treatment and Outcome of Coital Injuries of the Female Genital Tract Consecutive to Consensual Sexual Intercourse in the Limbe Regional Hospital

Abstract: IntroductionNonobstetrical genital injuries are gradually becoming a common cause of genital injuries. Consensual sex has been reported to be a possible cause of this type of injuries, but its contribution to traumatic lesions of the female genital tract is not well known. It has been suggested that injury consecutive to consensual sex can be extensive and life‐threatening.AimThe aim of this study was to analyze the clinical features, treatment modalities, and the outcome of injuries to the female genital trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…In the literature, the frequency of blood transfusions was frequently performed in case series (14). Tchounzou et al reported the blood transfusion rate as 5.6% in the coitius injury study of 53 diseases (15). In some studies, it was observed that this rate increased up to 38% (1, 15).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the frequency of blood transfusions was frequently performed in case series (14). Tchounzou et al reported the blood transfusion rate as 5.6% in the coitius injury study of 53 diseases (15). In some studies, it was observed that this rate increased up to 38% (1, 15).…”
Section: Discussionmentioning
confidence: 99%
“…Existen diferentes factores de riesgo que pueden favorecer la aparición de lesiones durante las relaciones sexuales: factores mecánicos como posiciones coitales, desproporciones anatómicas, uso de cuerpos extraños o postmenopausia [2][3][4] ; psicosomáticos como nerviosismo o torpeza; y causa mixta como pueden ser los casos de coitos apresurados o durante la primera relación sexual.…”
Section: Factores De Riesgounclassified
“…1 Very few cases have been reported in Cameroon and none in the west region of the country (to the best of our knowledge). [2][3][4] Non-obstetric vulvar hematomas (NVHs) are usually caused by direct trauma to the vulva during consensual or forceful sex/coitus and falls in squatting position. 1,5 The loose connective tissue of the vulva is prone to accumulation of blood and expansion of the hematoma.…”
Section: Introductionmentioning
confidence: 99%